CONTRACT DISTRIBUTION SYSTEM FRAMEWORK WITH CASE STUDY ON PC BUILDING MARKET - Khalif Amir, Zakry (Universiti Malaysia Sarawak (UNIMAS), 2019)
The focus of this FYP project is to establish a Contract Distribution System Framework that provides someone with adequate proficiency in IT or a small startup company, a generic foundation to build upon their own personalized Contract Distribution System. Grab, Airbnb, and Fiverr are Contract Distribution Systems that have been specialized into their own specific niche. This Contract Distribution System Framework will provide the base and generic features common among commercially available Contract Distribution Systems thus making development shorter and enabling the creation of Minimal Viable Products for validating business ideas, quicker. As a show of concept for this framework, the use case of a PC Building Market is chosen for its potential of being a commercially viable application mixed with the support from the rising trend of desktop live streaming, gaming entertainment and electronic sports.